A Deep Learning Development for Automatic License Plate Detection with Text Extraction Capability: Automatic License Plate Detection with Text Extraction Capability - DOKHAN, SABRI; Arbaiy, Nureize (Applied Information Technology And Computer Science, 2024)
Vehicle identification and tracking are essential in traffic surveillance systems, which prioritize safety and efficiency. Security personnel still manually observe medium-sized structures. Security officers physically record license plate numbers after visually examining passing automobiles. This process is time-consuming and error prone. This project aims to create a web-based deep learning system for automated license plate identification with text extraction at UTHM, Malaysia. A variety of car license plates will train the system. A convolutional neural network will immediately detect and interpret license plate text. The user may submit a vehicle photo to the online interface, and the system will recognize the license plate number and return a picture with the highlighted plate. The system will be tested on a set of concepts using accuracy and precision criteria. Traffic management and vehicle identification might employ the created technology.